1989
DOI: 10.1159/000167988
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Renal Cystic Disease in End-Stage Renal Disease: An Autopsy Study of 155 Cases

Abstract: Autopsy reports on 155 successive end-stage renal disease (ESRD) patients and 147 control patients without ESRD, matched for age, race and gender, were collected. Cystic transformation of the kidneys was noted in 58% of the ESRD patients and 13.6% of the control patients. There were 25 ESRD patients with renal adenoma and 3 with renal cell carcinoma. The single best predictor of cystic transformation or tumorous degeneration was patient’s age. A statistically significant association between cystic transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…This high incidence is definitional; their series included only advanced cases of ACKD. Numerous studies of ACKD in the dialysis population have shown that the incidence of ACKD is proportional to dialysis interval, with close to 100% of patients affected by 10 yr of dialysis (85)(86)(87)(88)(89)(90)(91)(92)(93)(94). Renal transplantation seems to reduce the incidence of ACKD (95).…”
Section: Eskd and Ackdmentioning
confidence: 99%
“…This high incidence is definitional; their series included only advanced cases of ACKD. Numerous studies of ACKD in the dialysis population have shown that the incidence of ACKD is proportional to dialysis interval, with close to 100% of patients affected by 10 yr of dialysis (85)(86)(87)(88)(89)(90)(91)(92)(93)(94). Renal transplantation seems to reduce the incidence of ACKD (95).…”
Section: Eskd and Ackdmentioning
confidence: 99%
“…In the case we report on, the size and weight of the kidney were entirely unusual. In autopsy studies where kidneys are weighed, the maximum weight reported was 380 g [8,9]. In a CT scan study, renal volume calculated was greater than nor mal (330 ml) in a single case (658 ml) for which unfortu nately we do not have any information [10], In the Ishikawa [11] study, the largest kidney volume accompa nying ARCD was 1,302 ml but 2 kidneys were involved.…”
Section: Discussionmentioning
confidence: 99%
“…One of these new entities to have appeared in the past few years is acquired renal cystic disease (ARCD) which is caused by the progressive sub stitution of the 'contracted' and atrophic renal paren chyma by multiple bilateral cysts. The importance of this entity lies in its potential complications: renal hemor rhage [1] and possible neoplastic degeneration [2][3][4]. Interest in this disease sparked following the work of Dunnill et al [5] in 1977, which was carried out on necropsy material and which revealed an incidence of the disease of up to 46 % in patients undergoing hemodi alysis.…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not the disease regresses following renal transplantation is a controversial question [7,19], Other predisposing factors, described in publications, are: be ing of the male sex [4,17], being elderly [3,4,17], having glomerular [6,8] or hypertensive etiology [3], and like wise having analgesic nephropathy [7], Perhaps one of the most significant aspects of this entity, however, is that which refers to its possible neo plastic degeneration, represented by both benign tumors (7.5% of cases undergoing dialysis) and malignant tu-mors (2.7%). These lesions show mild metastasizing capacity [6].…”
Section: Introductionmentioning
confidence: 99%